2019
DOI: 10.1080/09692290.2018.1560352
|View full text |Cite
|
Sign up to set email alerts
|

US-China conflict in global trade governance: the new politics of agricultural subsidies at the WTO

Abstract: This article shows how China's rise has radically altered the politics of one of the most prominent and controversial issues in the global trading system: agriculture subsidies. Agriculture subsidies depress global prices and undermine the competitiveness and livelihoods of poor farmers, and therefore have been long seen as a symbol of the injustice of the trading system. The issue has traditionally been understood in North-South terms, with developed countries seen as the perpetrators of harm and developing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 18 publications
0
13
0
7
Order By: Relevance
“…Nevertheless, China's behavior will certainly shift the lowest common denominator regarding the kind of liberal compromise that the WTO stands for. This influence of course does not preclude the fact that the future trajectory of the WTO will also depend on the direction in which other major trading nations move as well as the emergence of new conflict lines that cut across the North-South divide (Hopewell, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, China's behavior will certainly shift the lowest common denominator regarding the kind of liberal compromise that the WTO stands for. This influence of course does not preclude the fact that the future trajectory of the WTO will also depend on the direction in which other major trading nations move as well as the emergence of new conflict lines that cut across the North-South divide (Hopewell, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, developing countries have put pressure on Western nations to further liberalize their agricultural sector, and to revise existing rules on agricultural subsidies accordingly (Narlikar, 2010). Since the beginning of the round, however, North-South conflict lines have become blurrier as emerging countries, most notably China, introduced their own subsidy schemes (Hopewell, 2019). Chinese subsidies, including seed subsidies, direct payments and agricultural input subsidies, increased from RMB 14.5 billion in 2004 to RMB 167.5 billion in 2014 (Li, 2017).…”
Section: The Conflict Over Chinese Subsidies In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…They found that US-China tariff escalation could reduce global exports by up to 3% and global income by up to 1.7%. Hopewell (2019) studied the new politics of agricultural subsidies at the WTO, explaining how they evolve around the conflict between the US and China. The study claims that the trade conflict between these two dominant powers has thwarted the efforts of establishing a better set of disciplines on agricultural subsidies, thus had negative effects on the developing economies.…”
Section: Uluslararası İktisadi Ve İdari İncelemeler Dergisimentioning
confidence: 99%
“…The other issue is that this is influenced Ð for better or worse Ð by ChinaÕs own ongoing development. On the one hand, the competitive dislocations wrought by the countryÕs sheer scale creates acute challenges for other developing countries in just about every economic sector, and especially agriculture (Hopewell 2019). Yet on the other hand, now that it is so wealthy, Chinese policymakers stress their responsibility to pull other developing countries up too, particularly given that many of them recognised the sovereignty of the PRC when it was difficult to do so.…”
Section: Dual Identities: ôNeither Leading Goat Nor Stumbling Blockõmentioning
confidence: 99%